THE CONCEPT AND IMPORTANCE OF EDUCATIONAL ADMINISTRATION IN IMPROVING THE QUALITY OF EDUCATIONAL INSTITUTIONS: A THEORETICAL AND PRACTICAL REVIEW - Yeza, M. Farhan; Ghifari, Zafran; Karen, Febfiola; Hidayatullah, Rully (Sindoro: Cendikia Pendidikan, 2024)
This article discusses the concept and importance of educational administration in improving the quality of educational institutions, with a focus on both theoretical and practical perspectives. Educational administration is defined as the process of planning, organizing, implementing, and supervising various educational activities to ensure effective and efficient management. The article explores key concepts such as strategic planning, organizational structuring, leadership in execution, and monitoring and evaluation processes within educational settings. Furthermore, the significance of educational administration is highlighted through its impact on operational efficiency, teaching quality, strategic educational planning, human resource development, and institutional innovation. Theoretical insights are drawn from management theories, emphasizing the role of leadership and adaptability, while practical examples demonstrate the application of administrative strategies in successful schools. The article concludes by stressing the critical role of educational administration in fostering a high-quality educational environment, where ongoing challenges such as technological integration and social changes are met with effective leadership and administrative support.